Effect of purple loosestrife (Lythrum salicaria) diet supplementation in rabbit nutrition on performance, digestibility, health and meat quality. (10th September 2015) - Kovitvadhi, A.; Gasco, L.; Ferrocino, I.; Rotolo, L.; Dabbou, S.; Malfatto, V.; Gai, F.; Peiretti, P. G.; Falzone, M.; Vignolini, C.; Cocolin, L.; Zoccarato, I.
Abstract : In this study, 160 Hycole weaned rabbits (35 days old) were randomly divided into four groups of 40. The rabbits were studied throughout a 54-day experimentation period in order to determine the impact of dietary supplementation from herbs composed of 0.2%, 0.4% dry ground Lythrum salicaria leaves (LS) and 0.3% Cunirel ® (CR; a commercial herb mixture containing LS as the main ingredient) on performance, digestibility, health and meat quality. The basal diet was given to the control group. No significant differences were found in performance, 10 rabbits from each group were selected for evaluation regarding apparent digestibility. The rabbits fed the control diet and the diet with the low level of LS had a higher level of CP digestibility than did the animals that were supplemented with the high LS levels and CR (85.7% and 84.9% v . 84.0% and 84.0%, respectively; P <0.05). The ether extract digestibility was lower in the treatment group with 0.4%LS addition and CR as compared with the control group (52.2% and 54.5% v . 62.6%, respectively; P <0.05). The slaughter process was performed on 89-day-old rabbits to study the carcass characteristics, meat quality, blood parameters, caecal contents and gut histology. The total leukocyte counts in the control animals were lower than they were in the rabbits fed 0.2%, 0.4%LS and CR (4.06 v . 8.25, 8.63 and 8.21×10 9 /l, respectively; P <0.05). For caecal fermentation, the caecal contents of the rabbits fed 0.4% of LS, showed higher concentrations of total volatile fatty acid (VFA; 24.1 v . 18.9 mg/kg dry matter (DM); P <0.05) and acetic acid (18.3 v . 14.4 mg/kg DM; P <0.05), but lower ammonia levels (594 v . 892 mg/kg DM; P <0.05) as compared with the control group. PCR-denaturing gradient gel electrophoresis analyses were performed to evaluate the microbial community in hard faeces, collected at days 35, 42, 49, 56, 70 and 89, whereas the caecal contents were taken after slaughtering. The results demonstrated that between the treatment groups, the similarity of the microbial communities was higher as compared with the control group. Moreover, only age was shown to influence microbiota diversity. In conclusion, the results of this study indicated that supplementation of LS in rabbit diets leads to an increase in the total white blood cells, total VFA and acetic acid concentration, and a decrease in the ammonia levels, as well as the digestibility when CR and high level of LS were supplemented, without causing any adverse effects on other parameters.